Cosmetic tail docking: an overview of abuse and report of an interesting case (2016)
Background: This paper presents an overview of the global controversies surrounding cosmetic tail docking in puppies, some observed inconsistent practices among dog breeders and Veterinarians in West Africa, and the need for the African Veterinary Profession to take a decisive position on the cosmetic docking procedure. Case presentation: An interesting report of observed complications associated with cosmetic tail docking in a 3 week old male Boerboel is reported alongside the management of the ensuing complications. Conclusion: This paper highlights the still prevalent practice of cosmetic tail docking and seeks to enlighten clinicians towards stemming its abuse in Africa